2019
DOI: 10.1021/acs.est.9b03864
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Fractionation of Soil Arsenic from Natural and Anthropogenic Sources: Chemical Extraction, Scanning Electron Microscopy, and Micro-XRF/XAFS Investigation

Abstract: A large amount of excavated soils with low-level As contamination caused by civil construction projects is of great concern in Japan. This study investigated the chemical speciation and extractability of As in 24 soil samples from the sites affected and unaffected (naturally contaminated) by anthropogenic pollution. The results of As K-edge XANES demonstrated that naturally contaminated soils were grouped into two types: (i) soils containing FeAsS-like and As2S3-like species (ave. 53%, hereafter As-S species) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…, 17 and the mineralization of FeAsS and As 2 S 3 -like species in soil results in its pollution with As. 188…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 17 and the mineralization of FeAsS and As 2 S 3 -like species in soil results in its pollution with As. 188…”
Section: Resultsmentioning
confidence: 99%
“…Arsenic in soils results from anthropogenic activities, and the main sources in the soil are naturally occurring minerals, such as arsenopyrite, gelignite, realgar, orpiment, etc., 17 and the mineralization of FeAsS and As 2 S 3 -like species in soil results in its pollution with As. 188 The major inputs of As in soil are associated with burning of fossil fuels and biomass, mining activities, industrial effluents, use of pesticides (e.g. monosodium methyl arsenate, disodium methyl arsenate and cacodylic acid) in agriculture, lumber preservatives (e.g.…”
Section: Sample Collection Preservation and Pretreatmentmentioning
confidence: 99%
“…The soil samples were freeze-dried and screened through 100 mesh. One-step extraction (0.05 mol/L EDTA, 0.43 mol/L HNO 3 and 0.01 mol/L CaCl 2 ) 32 and sequential-steps extraction (BCR method) 33 were used to analyze the Pb availability in soil. The extraction solution was filtered by 0.22 μm and determined by ICP-MS (PlasmaQuant MS, Analytik-Jena, Germany).…”
Section: Soil Experiments Soil Samples (Properties Are Shown In Tablementioning
confidence: 99%
“…Several workers have reported on As speciation in soils and sediments. A study to investigate the chemical speciation and extractability of As in 24 soil samples from sites potentially affected by anthropogenic pollution in Japan has been reported by Itabshi et al 83 The results of As K-edge XANES demonstrated that naturally contaminated soils were grouped into two types: (i) soils containing FeAsS-like and As 2 S 3 -like species (average 53%) and (ii) soils with no or minor As-S species (average 3%). Clear differences were found in As, Fe, and S fractionation by sequential extraction.…”
Section: Arsenicmentioning
confidence: 99%